Aqueous humor flow rate in normal cats and the effect of topical 2% dorzolamide on aqueous humor flow and intraocular pressure - Crumley, William R. (Kansas State University, 2011)
Objective - To establish the aqueous humor flow rate in normal cats via fluorophotometry, utilizing a noninvasive method previously established in other species and to evaluate the effect of topical 2% dorzolamide on aqueous humor flow rate and intraocular pressure (IOP) in normal cats. Animals - 20 clinically normal domestic shorthair cats. Procedures – Topical administration of 10% sodium fluorescein was performed using a 3-drop protocol to establish its use in this species. Aqueous flow was measured using fluorophotometry in the right and left eyes. The subjects were then divided into 2 groups: the first received topical 2% dorzolamide (Trusopt®) and the second received topical artificial tear solution (control). The study was divided into two phases: a 3 day acclimation phase (no treatments given) and a 5 day treatment phase (treatments given three times daily). IOP measurements were taken at 7am, 10am, 1pm, 5pm, and 9pm throughout all phases of the study. Fluorophotometry was performed to measure the aqueous flow rate just prior to and at the end of the treatment phase (days 3 and 9 respectively). Results - The calculated aqueous humor flow rate for normal cats in the right, left, and both eyes was 5.94 ± 2.30 μl/min, 5.05 ± 2.06 μl/min, and 5.51 ± 2.21 μl/min, respectively. No significant differences were noted between the right and left eyes. In the dorzolamide group, the average flow rate during treatment (3.47 + 1.50 μl/min ) was significantly lower than prior to treatment (5.9 + 2.20 μl/min)(P < 0.001). The mean IOP during treatment (11 + 3 mmHg) was significantly lower than the mean IOP prior to treatment (15 + 3 mmHg)(P < 0.001). In the control group, there were no significant differences in aqueous humor flow or IOP values before or during treatment. Conclusions - The technique utilized for this study met the standard for accurate fluorophotometric calculation of aqueous humor flow. The average aqueous humor flow rate for normal cats calculated in this study was 5.51 ± 2.21 μl/min. Topical 2% dorzolamide significantly lowers aqueous humor flow (a 41% reduction) and IOP (a 26% reduction) in normal cats.
Keywords: Veterinary medicine; Aqueous humor flow; Fluorophotometry; Feline; Dorzolamide; Veterinary Medicine (0778)